Mindfulness, character, and workplace happiness: the moderating role of baseline levels of employee wellbeing - Lucas Monzani; Ana Ruiz Pardo; Sonja Bruschetto; Cassandra Ellis; Jordi Escartin; Jordi Escartin (Frontiers in Organizational Psychology, 2024)
Following the logic of the “happy-productive worker” hypothesis, organizations have been increasingly interested in new ways to elicit employee wellbeing. Consequently, research on mindfulness in work contexts has been burgeoning in recent years, as both conceptual and empirical reviews substantiated its importance as a cost-effective approach to promoting employee wellbeing. The purpose of the present study was to investigate whether employee happiness extends or transcends the conventional notions of employee wellbeing. More specifically, we invoke the positive psychology literature to argue that (a) employee happiness is related but distinct from employee wellbeing and (b) that initial levels of employee wellbeing might moderate the effect of mindfulness-based interventions. We conducted a secondary analysis of a publicly available dataset to test our predictions: focusing on 35 healthcare professionals from a healthcare organization in Barcelona, Spain. More precisely, employing a multivariate hierarchical regression, we compared if the incremental effect of an eight-week mindfulness-based strength intervention (MBSI) over a Mindfulness-based intervention (MBI) might be moderated by employees' initial levels before the intervention starts. Our results supported a moderating effect of employees' initial psychological wellbeing on a MBSI versus MBI. Implications for theory and practice are discussed.